2019
DOI: 10.1016/j.dhjo.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring issues relating to disability cultural competence among practicing physicians

Abstract: Background: Many factors contribute to the well-recognized health care disparities experienced by persons with disability, including failure of physicians to understand the lives of individuals with disability. Disability cultural competence considers physicians' ability to meet the social, cultural, and linguistic needs of this population.Objectives: To assess physicians' understanding of disability cultural competence and attitudes towards patients with disability. Methods:Qualitative analyses of open-ended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Participants' recommendations for other persons with pre‐existing mobility disability who develop cancer suggested that people recognize the importance of personal awareness of health status and care needs, placing responsibility on patients to prepare for appointments (i.e., preparing informed questions for clinicians) and feeling comfortable switching care teams to ensure sufficient accommodations. Participants concurred about the importance of self‐advocacy, especially given erroneous assumptions and attitudes about disability that may permeate care settings 23 . Attitudinal barriers can impact clinician‐patient trust, affecting patient satisfaction with care 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Participants' recommendations for other persons with pre‐existing mobility disability who develop cancer suggested that people recognize the importance of personal awareness of health status and care needs, placing responsibility on patients to prepare for appointments (i.e., preparing informed questions for clinicians) and feeling comfortable switching care teams to ensure sufficient accommodations. Participants concurred about the importance of self‐advocacy, especially given erroneous assumptions and attitudes about disability that may permeate care settings 23 . Attitudinal barriers can impact clinician‐patient trust, affecting patient satisfaction with care 24 .…”
Section: Discussionmentioning
confidence: 97%
“…21 The negative attitudes of health care providers and use of outdated terms is discouraging and remains a significant barrier to effective care for patients with disabilities. 3,22,23 Additionally, adults with disabilities are substantially more likely to categorize their health as fair or poor (40.3%) when compared to those without disabilities (9.9%) and are more likely to delay seeking health care due to cost. 24,25 Physical accessibility also remains a significant challenge, as evidenced by a study in California demonstrating that out of a sample of 2,400 primary care clinics in California, more than half lacked full physical accessibility.…”
Section: Current State Of Health Care For Individuals With Disabilitiesmentioning
confidence: 99%
“…One study demonstrated that patients with disabilities were more likely than those without disabilities to feel that the doctor did not listen to them, did not involve them in the treatment plan, and did not adequately explain treatments 21 . The negative attitudes of health care providers and use of outdated terms is discouraging and remains a significant barrier to effective care for patients with disabilities 3,22,23 . Additionally, adults with disabilities are substantially more likely to categorize their health as fair or poor (40.3%) when compared to those without disabilities (9.9%) and are more likely to delay seeking health care due to cost 24,25 .…”
Section: Current State Of Health Care For Individuals With Disabilitiesmentioning
confidence: 99%
See 2 more Smart Citations